FAKTOR-FAKTOR PENYEBAB PENGABAIAN NAFKAH SUAMI TERHADAP ISTRI KARIR MENURUT PANDANGAN HUKUM ISLAM (Penelitian di Kecamatan Trienggadeng kab. Pidie Jaya) - Fazlon Umar (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2023)
This research examines the impact of ignoring the husband's maintenance on career wives in the view of Islamic law. A husband has the obligation to provide for his wife both in terms of clothing, food and shelter according to his ability. There are times when a husband ignores his wife's maintenance because the wife has her own income. A career wife should still earn a living from her husband because the wife works to help her husband with family economic problems. The husband's actions have their own impact on the lives of married couples. This study has 2 problem formulations: first, what are the factors that cause career wives to neglect their livelihood. Second, what is the impact of neglecting a living on a career wife. In this study, the authors used qualitative research, using field research and library research methods. The results of the study stated that a husband should not ignore the maintenance of his wife, even though the wife is a worker who has her own income. Ibn Qudamah said: Scholars agree on the husband's obligation to support his wives when he reaches puberty, unless the wife commits disobedience. Neglecting a living has a negative impact on the integrity of the household, especially the wife who begins to find it difficult to respect her husband, harmony in the household fades and decreases due to a wife's non-fulfillment of income. From the explanation above, it can be concluded that neglecting maintenance should not be done because maintenance is a husband's obligation to his wife, which is definitely stated in the Al-Qur'an and Hadith. Keywords. Livelihood of Husband and Wife, Views of Islamic Law.